SAT0479 Early Findings from Prolia® Post-Marketing Safety Surveillance for Atypical Femoral Fracture, Osteonecrosis of the Jaw, Severe Symptomatic Hypocalcemia, and Anaphylaxis. (10th June 2014) - Geller, M.; Wagman, R.; Ho, P.; Siddhanti, S.; Stehman-Breen, C.; Watts, N.; Papapoulos, S.
Abstract : Background: Prolia has marketing authorization in the EU, US, Canada, Japan, and over 40 countries or administrative districts worldwide for the treatment of postmenopausal women with osteoporosis at high/increased risk for fracture. Since product registration, new data have provided further information about efficacy and safety. In the FREEDOM extension trial, 8 years of continued denosumab (Prolia) therapy was associated with continued increases in bone mineral density and maintenance of low fracture incidence. Rates of adverse events did not increase over time. 1 In addition, a rigorous pharmacovigilance program has been established to complement safety data collection from clinical trials. Spontaneous adverse event reports, while often with insufficient information, are the cornerstone of safety surveillance programs and help detect rare and serious adverse drug reactions (ADR). Objectives: We characterize post-marketing (PM) experience for 4 ADRs with Prolia: atypical femoral fracture (AFF), osteonecrosis of the jaw (ONJ), severe symptomatic hypocalcemia (SSH), and anaphylaxis. Methods: The Amgen PM database undergoes continual assessment of adverse events reported from health care providers, patients, and other sources. AFF and ONJ cases were assessed and adjudicated by independent committees. SSH and anaphylaxis prompted further assessment by Amgen Global Safety because causality due to Prolia could not be excluded. Results: As of September 2013, estimated exposure with Prolia was 1, 252, 566 patient-years. Four PM reports have been adjudicated as consistent with the ASBMR definition for AFF. 2 All patients had prior bisphosphonate (BP) use. Two subjects had healing and two did not have follow-up information. For ONJ, 32 PM reports were adjudicated as consistent with the AAOMS definition. 3 Risk factors included ≥1: glucocorticoids, chemotherapy, prior BP use, older age, and invasive dental procedures. One-third of reports indicated resolution, 1/3 were ongoing, and the remainder were unknown. Eight reports of SSH included symptoms of seizures and/or tetany; nearly all (7 of 8) had chronic kidney disease, a risk factor for hypocalcemia; most SSH events occurred within 30 days of Prolia administration and responded to IV/PO calcium/vitamin D. For anaphylaxis, 5 reports included hypotension, dyspnea, throat tightness, facial and upper airway edema, pruritus, and/or urticaria. Most events occurred within 1 day of the first Prolia dose; emergency room treatments included antihistamines and IV/PO steroids with no fatal outcomes. Conclusions: These PM events with Prolia have not shown any unexpected findings; the benefit/risk profile for Prolia remains favorable. Ongoing safety surveillance will continue in the clinical trial program and pharmacovigilance activities. References: Papapoulos et al., JBMR 2013. Shane et al., JBMR 2010. Position Paper, AAOMS 2009. Disclosure of Interest: M. Geller Shareholder of: Amgen Inc., Employee of: Amgen Inc., R. Wagman Shareholder of: Amgen Inc., Employee of: Amgen Inc., P. Ho Shareholder of: Amgen Inc., Employee of: Amgen Inc., S. Siddhanti Shareholder of: Amgen Inc., Employee of: Amgen Inc., C. Stehman-Breen Shareholder of: Amgen Inc., Employee of: Amgen Inc., N. Watts Shareholder of: OsteoDynamics, Grant/research support: Merck, NPS, Consultant for: AbbVie, Amarin, Amgen, Bristol-Meyers Squibb, Corcept, Endo, Imagepace, Janssen, Lilly, Merck, Novartis, Noven, Novo Nordisk, Pfizer/Wyeth, Quark, Radius, sanofi-aventis, S. Papapoulos Consultant for: Amgen, Axsome, Gador, GSK, Merck, Speakers bureau: Amgen, Eli Lilly, GSK, Merck, Novartis DOI: 10.1136/annrheumdis-2014-eular.1170